Estudo do comportamento tribológico de materiais vitrocerâmicos - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2022)
Glass-ceramics materials are composed of crystals and one glass matrix. They are produced by anneling treatment of the parent glasses. In general, it is necessary two heat treatments, one to nucleate and another to grow the nucleated crystals. Controlled crystallization makes possible the creation of a material with various properties for numerous applications. Lithium disilicatebased glass-ceramics were the first glass-ceramics to be produced and they are considered fundamental to understanding the glass-ceramics properties. Furthermore, lithium disilicate glassceramics (LS2) are widely used as dental implants, due to their good aesthetic and great fracture toughness (KIC). This thesis presented the study of the LS2 tribological properties under a dry environment. The pin-on-disc tribometer was used with 5 cm/s of the linear sliding speed. At first, the influence of crystal size on the tribological properties was study for a constant crystallized volume fraction (64 ± %). Alumina and ungsten carbide (WC) were used as counterface, with an applied load of 5 N. The obtained results shown a great variety of the tribological properties with the counterface. Moreover, it was observed a slight decrease of wear with the crystal size increase. After these first tests, only an alumina counterface was used. The influence of the crystallized volume fraction, sliding distance and applied load were verified. It was observed an abrupt increase of COF in the samples with crystallized volume fraction lower than 70 %. It was determined that this behavior was characteristic of the studied tribologic system and it was related to abrasive wear by fragile fracture. The applicability of Archard’s Equation to describe the corrent glass-ceramics was studied with the variation of the applied load. The wear mechanisms were determined by the variation of the sliding distance. In addition, glass-ceramics of lithium meta- and disilicate were tested and their results were compared with the commercial glass-ceramics IPS e.max CAD (Ivoclar Vivadent). The sample of lithium metasilicate shows better results than the commercial sample, and could be applied as a dental prosthesis. A tribological study was made with artificial marble formed from a mix of recycle glass and minerals (albite, alumina, petalite, and quartz). At the last chapter of the thesis, the first results about the tentative clinoenstatite crystallization in MgO − Al2O3 − SiO2 glass-ceramics are presented.
Keywords: Dissilicato e metassilicato de lítio; tamanho de cristal; fração volumétrica cristalizada; Equação de Archard; mecanismos de desgaste; IPS e.max CAD; MgO − Al2O3 − SiO2; clinoenstatita; Lithium di- and metasilicate; crystal size; crystallized volume fraction; Archard Equation; wear mechanism; IPS e.max CAD; MgO − Al2O3 − SiO2; clinoenstatite; CNPQ::CIENCIAS EXATAS E DA TERRA::FISICA